Perception of Teachers' Attitudes and Training Competence of Teachers in the Field of Mathematics - Javier Sánchez-Mendías; Antonio Miñán-Espigares; Sonia Rodríguez-Fernández (MDPI AG, 2024)
This article presents the results of a study on the perception that future teachers have in relation to the attitudes their teachers showed towards mathematics during the Primary Education stage, their level of competence in mathematics, and the possible relationship between both variables. A questionnaire was administered to a sample of 488 future Primary School teachers, subjecting the obtained data to a descriptive, multivariate, and inferential analysis in order to know the perception of these attitudes, establish subject profiles, and know the incidence between this variable and mathematical competence. The future teachers show an ambivalent perception of their teachers' attitude towards mathematics. Three profiles of subjects with negative, neutral, and positive perception are set, with almost half of the sample included in the first two profiles. In the inferential study, values that reflect a significant incidence between both variables are obtained. It is important that teachers convey favourable attitudes towards mathematics to their students, since the more favourable they are, the better the levels of competence obtained. To minimise this deficit, content and activities aimed at improving mastery and encouraging the development of favourable attitudes towards this discipline through specific actions should be incorporated into training programs.